2016
DOI: 10.2196/jmir.5904
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Suicidal Ideation in People Seeking Web-Based Help for Suicidality: Secondary Analysis of a Dutch Randomized Controlled Trial

Abstract: BackgroundSuicidal ideation (SI) is a common mental health problem. Variability in intensity of SI over time has been linked to suicidal behavior, yet little is known about the temporal course of SI.ObjectiveThe primary aim was to identify prototypical trajectories of SI in the general population and, secondarily, to examine whether receiving Web-based self-help for SI, psychiatric symptoms, or sociodemographics predicted membership in the identified SI trajectories.MethodsWe enrolled 236 people, from the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
(42 reference statements)
2
7
1
Order By: Relevance
“…However, baseline level of depression did not impact the effectiveness of the intervention, although the possibility remains that suicidal severity could interfere with program completion. It should also be noted here that the Dutch trial found more pronounced effects for severe suicidality [ 13 , 32 ], which contradicts the current findings. Another possibility relates to help-negation, which is the decreased propensity to engage in help-seeking behaviors as a consequence of more severe levels of suicidal ideation.…”
Section: Discussioncontrasting
confidence: 99%
“…However, baseline level of depression did not impact the effectiveness of the intervention, although the possibility remains that suicidal severity could interfere with program completion. It should also be noted here that the Dutch trial found more pronounced effects for severe suicidality [ 13 , 32 ], which contradicts the current findings. Another possibility relates to help-negation, which is the decreased propensity to engage in help-seeking behaviors as a consequence of more severe levels of suicidal ideation.…”
Section: Discussioncontrasting
confidence: 99%
“…Four distinct trajectories of suicidal ideation were identified, consistent with previous trajectory analysis in clinical trials in community-based adult populations (Allan et al, 2018; Kasckow et al, 2016; Madsen et al, 2016b). Almost two-thirds of participants were assigned to trajectories (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…Suicidal ideation is often a feature of depression, with suicidal ideation a risk factor for self-harm (Ribeiro et al, 2016; Witt et al, 2018) and suicide (Ribeiro et al, 2016). Suicidal ideation severity is known to fluctuate (Selby and Yen, 2014), including over the course of evidence-based treatment for depression (Vitiello et al, 2009), and treatment-mediated improvements in depression symptomatology do not necessarily equate to improvements in suicidal ideation severity (Batterham et al, 2017, 2019; Madsen et al, 2016a, 2016b; van Spijker et al, 2014). Given most effects of current evidence-based psychological and medication treatments for depression are modest (Locher et al, 2017; Weisz et al, 2017), earlier identification of clinically relevant subgroups of patients who are likely to benefit from alternative or additional treatment might facilitate tailored and more effective intervention to improve outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…While fit statistics for the GMMs identified a 2‐class solution for depressive symptoms and suicidal ideation, 3–4 class solutions are more frequently reported in the literature, based on a review of long term trajectories of depressive symptoms (Musliner et al., ) and recent studies reporting trajectories of suicidal ideation (Allan, Gros, Lancaster, Saulnier, & Stecker, ; Kasckow et al., ; Köhler‐Forsberg et al., ; Madsen et al., ,b). This discrepancy in research findings may be explained by factors such as differences in measures used to assess symptoms, differences in follow‐up periods, differences in study design (e.g., observational studies vs. trials, and variable eligibility criteria), and differences in target populations (e.g., clinical vs. population samples).…”
Section: Discussionmentioning
confidence: 99%
“…If a causal relationship between depression and suicidal thinking exists, it would be expected that individuals who experience decreases in depressive symptoms would also have decreasing suicidal thoughts, and vice‐versa, such that the measures would be tethered over time. There has been an increasing interest in analyzing longitudinal trajectories of mental health symptoms to identify subgroups with distinctive patterns of symptoms, including depressive symptoms (see Musliner, Munk‐Olsen, Eaton, & Zandi, ) and suicidal thoughts (e.g., Kasckow et al., ; Madsen, Karstoft, Secher, Austin, & Nordentoft, ; Madsen, van Spijker, Karstoft, Nordentoft, & Kerkhof, ). However, we are not aware of studies that have analyzed these factors together to examine whether tethering occurs.…”
Section: Introductionmentioning
confidence: 99%